Bill Gates - L Harbo, Christopher (North Mankato Minnesota Capstone Press, 2014)
Simple text and photographs present the life of Bill Gates, founder of Microsoft"--
Famous people
a gift from book africa
1 2 13 15
Keywords: Bill & Melinda Gates Foundation -- History -- Juvenile literature; Gates, Bill -- 1955- -- Juvenile literature; Microsoft Corporation -- History -- Juvenile literature